If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5u=-1+4u
We move all terms to the left:
5u-(-1+4u)=0
We add all the numbers together, and all the variables
5u-(4u-1)=0
We get rid of parentheses
5u-4u+1=0
We add all the numbers together, and all the variables
u+1=0
We move all terms containing u to the left, all other terms to the right
u=-1
| 18.6t+16.15=10.1t | | 10=7-3u | | x+2=2x−1 | | 2f+-7=3 | | +2=2x−1 | | -3(x-1)+8(x-3)=6x+7-6x | | 3x+4x=14+2x+11 | | -3+8t=9+9t | | -444=6(9x+16) | | 2f=-18+3f | | -10c=-9c+7 | | -9=-1/3x+16 | | 14w-15=13w | | -11s+2=2-14s | | 3/x-1=6 | | 3g-10.72=2.2g-19.36 | | 132=100+n | | -12-7v=10-9v | | x-49=32 | | 10u=14+9u | | -8k=-4-7k | | -252=6(-10x+8) | | -9+4b=20-8b-5 | | 7(5a-4)-1=14-81 | | -5.5r-15.82=0.02+3.48+3.7r | | 38=4x=10 | | -9r-8+4r=-4r+2 | | 23=4y-1 | | 6=9x/9 | | z/3-9=-7 | | z-8=10z+10 | | 12+2(2x-2)=4(1+4x)-20 |